Jakobson Revisited: Poetic Distinctiveness, Modes of Operation, and Perception - Kraxenberger, Maria (Rivista Italiana di Filosofia del Linguaggio, 2014)
The present paper aims to approximate an understanding of poetry’s distinctiveness and its specific modes of operation in regard to the poetic text as well as its perception.Here it follows the writings of Roman Jakobson, and distinguishes between poetic and prosaic language use with respect to the communicative function in poetry, textual defamiliarizing effects, and their functional and perceptual consequences. By referring both to Victor Shklovsky’s psychological concept of ostranenie and Jakobson’s model of language functions, special attention is paid to the location ofemotions in poetic texts. Given this background, specific factors of communication as well as distinct emotional modes of operation can be distinguished. This is discussed using ratings of the poem Letzte Wache by Georg Heym that are takenfrom a survey study on emotional classification and aesthetic evaluation of poetry.Finally, extra-textual consequences of poetic devices are addressed and the fruitfulness of Jakobson’s writings for contemporary, interdisciplinary approaches is stressed to highlight the enduring relevance of his ideas.